(untitled) (Journal of history, 2019)
This paper asserts that the Soviet women emancipation project was system interference into the Kazakh society traditional gender order. Its target was the Bolshevik’s intention redefines the Kazakh women roles traditionally played and at the end to establish the State control over her. For the implementation of this target Bolsheviks have enacted laws regulating the Kazakhs family-marriage system; involved women in public production, put into new motherhood practices. It was concluded that formation of women new identity was a part of holistic social constructing soviet policy.